Aromaticity and photophysics of tetrasila- and tetragerma-annelated tetrathienylenes as new representatives of the hetero[8]circulene family - Baryshnikov G. V. Gleb Vladimirovich; Valiev R. R. Rashid Rinatovich; Cherepanov V. N. Viktor Nikolaevich; Karaush N. N. Nataljya Nikolaevna; Minaeva V. A. Valentina; Minaev B. F. Boris Filippovich; Ogren Kh. Khans (2019, 2019)
Title screen